Buoyancy Assisted Janus Membrane Preparation by ZnO Interfacial Deposition for Water Pollution Treatment and Self‐cleaning. Issue 21 (20th August 2019) - Pan, Tian‐Di; Li, Zong‐Jie; Shou, Da‐Hua; Shou, Wan; Fan, Jin‐Tu; Liu, Xuqing; Liu, Yong
Abstract: Water pollution, such as marine oil spill and organic chemicals pollution, is a worldwide challenge. To advance this emerging field, Janus membranes with asymmetric wettability, for oil–water separation, similitude of diode in electrocircuit, are fabricated by leveraging the buoyancy of poly(vinylidene fluoride) nanofiber on water/air interface. ZnO nanowires are in situ grown on the surface of nanofibers immersed in the solution, mimicking a nanoscale Setaria viridis structure. Such Janus membrane shows a good hydrophilicity/underwater oleophobicity on ZnO nanowires modified side and exhibits opposite hydrophobicity on the other side. Due to the side‐specific morphologies, this membrane can work either as "water‐removing" type or "oil‐removing" type filter as a diode in fluid. The membrane shows excellent permeability with the water and oil flux up to 1210 and 7653 L m −2 h −1, respectively, only driven by gravity. The durability of functional membrane is excellent and separation efficiency is higher than 97.24% after ten cycling tests. Furthermore, the hydrophilic side demonstrates an excellent photocatalytic performance over the degradation of rhodamine B dye, as self‐cleaning properties. This Janus membrane is to be an excellent candidate for wastewater remediation, both oil/water separation and organic pollutant decomposition. Abstract : ZnO@poly(vinylidene fluoride) (PVDF) Janus membrane is fabricated by electrospinning and hydrothermal reaction. The fabricated membrane with ZnO nanowires on PVDF nanofiber shows a good hydrophilicity/underwater oleophobicity on ZnO nanowires side and exhibits hydrophobicity on the other side. The membrane provides a scalable strategy for functional fluid diode fabrication which can be used for high efficient oil/water separation.